Transarterial Yttrium-90 Glass Microsphere Radioembolization of Chemotherapy-Refractory Breast Cancer Liver Metastases: Results of a Single Institution Retrospective Study - Barakat, Elie; Bibok, Andras; Rishi, Anupam; Ahmed, Altan; Frakes, Jessica M.; Hoffe, Sarah E.; Armaghani, Avan J.; Soyano, Aixa E.; Costa, Ricardo L.B.; El-Haddad, Ghassan; Choi, Junsung; Kis, Bela (Advances in radiation oncology, 2022)
Our purpose was to retrospectively evaluate the safety and efficacy of transarterial hepatic radioembolization (TARE) treatment with yttrium-90 labeled glass microspheres in patients with chemotherapy-refractory breast cancer with liver-dominant metastatic disease. This retrospective single-institution study evaluated 31 female patients (mean age of 59.6 ± 13.2 years) who were treated with TARE. All patients received and progressed on systemic chemotherapy before TARE. Twenty-one patients also had extrahepatic metastases, including 13 patients who had metastases in bones only besides the liver. Survival data were analyzed by Kaplan-Meier method and compared using log-rank test. Imaging response to treatment was determined by Response Evaluation Criteria in Solid Tumors. Median overall survival (OS) from the TARE was 13 months (95% confidence interval, 9.1-16.9 months). The survival probability at 1, 2, and 3 years was 60.1%, 36.7%, and 24.5%, respectively. The median hepatic progression-free survival was 7 months (95% confidence interval, 6.1-7.9 months). There was no 30-day mortality and 3 patients (9.4%) had grade 3 toxicity. Estrogen receptor (ER) positive status predicted prolonged survival (14 months for ER+ vs 9 months for ER-; P = .028). Patients who had bone-only extrahepatic disease had higher OS than patients with extraosseous metastases (23 vs 8 months, P = .02). At the 3-month follow-up the radiographic objective response rate was 46.6% and disease control rate was 70%. The treatment of patients with liver-dominant chemotherapy-refractory breast cancer metastases with TARE using yttrium-90 labeled glass microspheres is safe and led to promising hepatic disease control and OS especially in patients with ER+ tumors and in patients without extrahepatic extraosseous metastases.